Massive Infiltrative Osteolysis of the Mandible in Oral Squamous Cell Carcinoma: A Case Report with a Review of the Literature - Smrithy Sivadas K; Ananya Madiyal; Vidya Ajila; Krishna Sharan; Yashika Jain (Precision Radiation Oncology, 2025)
Abstract Oral Squamous Cell Carcinoma (OSCC) is the most prevalent form of oral cancer, constituting over 90% of reported cases. This malignancy commonly infiltrates bone, making bone invasion a significant clinical issue. OSCC may invade bone via either an infiltrative or erosive pattern, with the pattern of invasion closely correlating with the clinical behavior of the disease and potentially holding prognostic value. Typically, OSCC spreads to the mandibular bone through direct infiltration of the alveolar ridge or lingual cortical plate. Interestingly, only 6% of OSCC cases initially present with a primary tumor, necessitating comprehensive whole‐body imaging and clinical examinations to exclude other primary tumors. This report details a rare case of long‐standing OSCC of the retromolar pad, which led to infiltrative osteolysis of the mandible, culminating in the near‐total disappearance of the bone in a 47‐year‐old male patient.